1970
DOI: 10.3126/nelta.v16i1-2.6132
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Activities for Teaching EFL Writing in a Context of Vietnam

Abstract: The article aims at pointing out what kinds of activities designed to improve the learners’ writing proficiency are effective in a Vietnamese context. With a two-group pretest and posttest design of an empirical research, the authors implemented a series of teaching activities in the classroom. The data were collected by means of pre-tests, post-tests, and interviews. The results indicated that the participants in the experimental condition significantly gained in their writing performance. Qualitative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Moreover, the study results expressed that students of government school must develop an understanding related to story writing and comprehensive writing. The results of the study conducted by Nguyen (2011) are also in-line with the findings of this study investigated that broaden reading exercises in English are additionally the subject to be proposed. Unmistakably reading and inscription consistently have close and corresponding connections.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the study results expressed that students of government school must develop an understanding related to story writing and comprehensive writing. The results of the study conducted by Nguyen (2011) are also in-line with the findings of this study investigated that broaden reading exercises in English are additionally the subject to be proposed. Unmistakably reading and inscription consistently have close and corresponding connections.…”
Section: Discussionsupporting
confidence: 87%
“…Many have investigated challenges to Vietnamese learners of English when it comes to writing. For example, they have to tackle the lack of vocabularies and ideas, limitations on grammatical knowledge, and less confidence (Nguyen et al 2011). Another problem is related to motivation as most students find writing difficult and unrewarding.…”
Section: Literature Review Efl Writing Teaching and Learning In Vietnammentioning
confidence: 99%
“…A number of methods and strategies have been implemented to help students sharpen their writing skill. Nguyen et al(2011) investigated the effect of numerous activities in EFL writing classes like free writing, pyramid sharing and deciding, group drafting, and peer support, and concluded that they contribute to the students' significant improvement in their writing performance. An action research conducted by Nguyen (2016) indicates that the implementation of critical thinking has positive impacts on students' attitudes to writing and their writing performance.…”
Section: Literature Review Efl Writing Teaching and Learning In Vietnammentioning
confidence: 99%
“…However, in most of the writing classes in Vietnam, students are passive in their writing skill. A lot of activities were implemented to improve students' writing skill but these ones are still not effective enough to encourage learners for this skill (Nguyen et al, 2011). Most of the teachers of English in Vietnam often claim that it is difficult to teach their students the writing skill.…”
Section: Introductionmentioning
confidence: 99%